DNA Damage Response and Immune Defense: Links and Mechanisms - Nakad, Rania; Schumacher, Björn (Frontiers in Genetics, 2016)
DNA damage plays a causal role in numerous human pathologies including cancer, premature aging and chronic inflammatory conditions. In response to genotoxic insults, the DNA damage response (DDR) orchestrates DNA damage checkpoint activation and facilitates the removal of DNA lesions. The DDR can also arouse the immune system by for example inducing the expression of antimicrobial peptides as well as ligands for receptors found on immune cells. The activation of immune signalling is triggered by different components of the DDR including DNA damage sensors, transducer kinases, and effectors. In this review, we describe recent advances on the understanding of the role of DDR in activating immune signalling. We highlight evidence gained into (i) which molecular and cellular pathways of DDR activate immune signalling, (ii) how DNA damage drives chronic inflammation, and (iii) how chronic inflammation causes DNA damage and pathology in humans.